Facile fabrication of biobased PNC-containing nano-layered hybrid: Preparation, growth mechanism and its efficient fire retardancy in epoxy. (January 2019) - Wang, Peng-Ji; Liao, Dui-Jun; Hu, Xiao-Ping; Pan, Ning; Li, Wen-Xiong; Wang, De-Yi; Yao, Yong
Abstract: A bio-based organic-inorganic hyperbranched hybrid (PAMA), possessing unique nano-layered structure, was designed and prepared by the neutralization reaction between phytic acid and melamine, then used as a multi-function intumescent flame retardant for epoxy resin (EP). FTIR, 1 H NMR, XRD, XPS, TGA and DSC were employed to investigate the chemical structure, growth mechanism and thermal behaviour of PAMA. SEM and TEM results confirmed the nano-layered structure of the PAMA. The limiting oxygen index (LOI) of EP incorporated with 6 wt% PAMA (EP-6) was 29.7%, and the UL-94 V-0 rating was also achieved. In contrast to the EP, the peak heat release rate (PHRR), total smoke production (TSP), and fire growth rate (FIGRA) of EP-6 were reduced by 62.3, 36.2, and 62.16%, respectively. The flame retardant mechanism of PAMA was further depicted using TG-FTIR and SEM/EDX techniques. In addition, the mechanical properties of EP composites are reinforced by the incorporation of PAMA. All the results demonstrate that the nano-layered PAMA is a high-efficient and eco-friendly fire retardant for EP. Graphical abstract: Highlights: An organic-inorganic hybrid with a unique nano-layered structure was first successfully synthesized via self-assembly. The growth mechanism of the nano-layered structure has been investigated comprehensively. Remarkable enhancements on flame retardancy and mechanical properties of epoxy resin were achieved.